x-2y=\(\sqrt{xy}\).tính giá trị của biểu thức : (\(\sqrt{x}+3\sqrt{y}\))(\(2\sqrt{x}-\sqrt{y}\))
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có : \(P=\sqrt{2x^2+xy+2y^2}+\sqrt{2y^2+yz+2z^2}+\sqrt{2z^2+xz+2x^2}\)
Xét : \(\sqrt{2x^2+xy+2y^2}=\sqrt{\dfrac{3}{4}.\left(x-y\right)^2+\dfrac{5}{4}.\left(x+y\right)^2}\)
\(\ge\sqrt{\dfrac{5}{4}.\left(x+y\right)^2}=\dfrac{\sqrt{5}}{2}.\left(x+y\right)\)
\(CMTT:\sqrt{2y^2+yz+2z^2}\ge\dfrac{\sqrt{5}}{2}.\left(y+z\right)\)
\(\sqrt{2z^2+xz+2x^2}\ge\dfrac{\sqrt{5}}{2}.\left(x+z\right)\)
Do đó : \(P\ge\dfrac{\sqrt{5}}{2}.\left(x+y+y+z+z+x\right)=\dfrac{2\sqrt{5}.\left(x+y+z\right)}{2}\)
\(\Rightarrow P\ge\sqrt{5}.\left(x+y+z\right)\)
Ta có : BĐT : \(\left(a+b+c\right)^2\ge3\left(ab+bc+ca\right)\)
\(\Rightarrow\left(x+y+z\right)^2\ge3\left(xy+yz+zx\right)\)
Mà : \(xy+yz+zx=3\)
\(\Rightarrow\left(x+y+z\right)^2\ge9\)
\(\Leftrightarrow x+y+z\ge3\)
\(\Rightarrow P_{min}=3\sqrt{5}\)
Dấu bằng xảy ra : \(\Leftrightarrow x=y=z=1\)
a) ĐKXĐ: \(x,y\ge0\)
\(M=\dfrac{x\sqrt{y}-\sqrt{y}-y\sqrt{x}+\sqrt{x}}{1+\sqrt{xy}}=\dfrac{x\sqrt{y}-y\sqrt{x}+\sqrt{x}-\sqrt{y}}{1+\sqrt{xy}}\)
\(=\dfrac{\sqrt{xy}\left(\sqrt{x}-\sqrt{y}\right)+\left(\sqrt{x}-\sqrt{y}\right)}{1+\sqrt{xy}}=\dfrac{\left(\sqrt{x}-\sqrt{y}\right)\left(1+\sqrt{xy}\right)}{1+\sqrt{xy}}=\sqrt{x}-\sqrt{y}\)
b) \(x=\left(1-\sqrt{3}\right)^2\Rightarrow\sqrt{x}=\sqrt{\left(1-\sqrt{3}\right)^2}=\left|1-\sqrt{3}\right|=\sqrt{3}-1\)
\(y=3-\sqrt{8}\Rightarrow\sqrt{y}=\sqrt{3-\sqrt{8}}=\sqrt{3-2\sqrt{2}}=\sqrt{\left(\sqrt{2}\right)^2-2.\sqrt{2}.1+1^2}\)
\(=\sqrt{\left(\sqrt{2}-1\right)^2}=\left|\sqrt{2}-1\right|=\sqrt{2}-1\)
\(\Rightarrow M=\left(\sqrt{3}-1\right)-\left(\sqrt{2}-1\right)=\sqrt{3}-\sqrt{2}\)
Có : \(x-2y-\sqrt{xy}+\sqrt{x}-2\sqrt{y}=0\)
\(\Leftrightarrow\left(\sqrt{x}-2\sqrt{y}\right)\left(\sqrt{x}+\sqrt{y}\right)+\sqrt{x}-2\sqrt{y}=0\)
\(\Leftrightarrow\left(\sqrt{x}-2\sqrt{y}\right)\left(\sqrt{x}+\sqrt{y}+1\right)=0\)
\(\Leftrightarrow\sqrt{x}=2\sqrt{y}\) (Do \(\sqrt{x}+\sqrt{y}+1>0,\forall x;y>0\))
\(\Leftrightarrow x=4y\)
Khi đó \(P=\dfrac{7y}{\left(2\sqrt{y}+3\sqrt{y}\right).\left(\sqrt{x}+2\sqrt{y}\right)}\)
\(=\dfrac{7y}{5\sqrt{y}.4\sqrt{y}}=\dfrac{7}{20}\)
\(P=\sqrt{\frac{1}{36}\left(11a+7b\right)^2+\frac{59\left(a-b\right)^2}{36}}+\sqrt{\frac{1}{36}\left(7a+11b\right)+\frac{59\left(a-b\right)^2}{36}}\)
\(=\sqrt{\frac{1}{16}\left(3a+5b\right)^2+\frac{5\left(a-b\right)^2}{16}}+\sqrt{\frac{1}{16}\left(5a+3b\right)^2+\frac{5\left(a-b\right)^2}{16}}\)
\(\ge\frac{1}{6}\left(11a+7b\right)+\frac{1}{6}\left(7a+11b\right)+\frac{1}{4}\left(3a+5b\right)+\frac{1}{4}\left(5a+3b\right)\)
\(=5\left(a+b\right)=5.2016=10080\)
\(\left(\sqrt{x}+3\sqrt{y}\right)\left(2\sqrt{x}-\sqrt{y}\right)=2x-\sqrt{xy}+6\sqrt{xy}-3y\)
\(=2x-3y+5\sqrt{xy}\)
\(=2x-3y+5.\left(x-2y\right)=2x-3y+5x-10y=7x-13y\)